Ankle taping can reduce external ankle joint moments during drop landings on a tilted surface - Sato, N.; Nunome, H.; Hopper, L. S.; Ikegami, Y. (Sports Biomechanics, 2019)
Ankle taping is commonly used to prevent ankle sprains. However, kinematic assessments investigating the biomechanical effects of ankle taping have provided inconclusive results. This study aimed to determine the effect of ankle taping on the external ankle joint moments during a drop landing on a tilted surface at 25°. Twenty-five participants performed landings on a tilted force platform that caused ankle inversion with and without ankle taping. Landing kinematics were captured using a motion capture system. External ankle inversion moment, the angular impulse due to the medio-lateral and vertical components of ground reaction force (GRF) and their moment arm lengths about the ankle joint were analysed. The foot plantar inclination relative to the ground was assessed. In the taping condition, the foot plantar inclination and ankle inversion angular impulse were reduced significantly compared to that of the control. The only component of the external inversion moment to change significantly in the taped condition was a shortened medio-lateral GRF moment arm length. It can be assumed that the ankle taping altered the foot plantar inclination relative to the ground, thereby shortening the moment arm of medio-lateral GRF that resulted in the reduced ankle inversion angular impulse.